ผลกระทบต่อหลักกฎหมายมหาชนอันเกิดจากคำวินิจฉัยของศาลรัฐธรรมนูญและองค์กรที่ทำหน้าที่ศาลรัฐธรรมนูญ ตามรัฐธรรมนูญแห่งราชอาณาจักรไทย (ฉบับชั่วคราว พุทธศักราช 2549 และรัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2550 - พูนเพิ่ม กฤษณะวณิช (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To investigate into the impact caused by the decision of the Constitutional Court by comparative study between the adjudication power vested by the Constitution and the judgment of Constitutional Court in the aspect of the compliance to the acceptable general principle of public law and its impact on the public law principles including to principle of constitutionality, principle of separation of power and the protection of civil liberties principle. The research shows that the decisions of the Constitutional Court and the organization forming as the Constitutional court under the Interim Constitution B.E. 2549 and Constitution B.E. 2550 effected significantly to the public law principle including to principle of constitutionality, principle of separation of power and the protection of civil liberties principle. The recommendation therefore, Firstly, Since the Interim Constitution B.E. 2549 and the Constitution B.E. 2550 was drafted and promulgated under the serious undemocratic environment and provide various provisions contradict to the principle of public law and democratic regime, The law application is only subjected to the constitutional provision but not also compliance with principle of public law and democratic regime. Thus it should be repealed and draft again by using the Constitution B.E. 2540 which is more appropriated as a main model. Secondly, It should increase the number of Justice who specialized in politics for more validity and legitimacy in considering the case highly involved to the politics. Thirdly, It should have the annual report of the Constitutional court presented to the parliament for reviewing and commendation. Fourthly, The related Law faculty in all universities should give more attention to the study of theory and application of public law interpretation because there are significant impact from the judgment of the Constitutional court.